Explorative Analyses of Nursing Research Data. (January 2017) - Kim, Hyeoneui; Jang, Imho; Quach, Jimmy; Richardson, Alex; Kim, Jaemin; Choi, Jeeyae
As a first step of pursuing the vision of "Big Data science in nursing, " we described the characteristics of nursing research data reported in 194 published nursing studies. We also explored how completely the Version 1 metadata specification of biomedical and healthCAre Data Discovery Index Ecosystem (bioCADDIE) represents these metadata. The metadata items of the nursing studies were all related to one or more of the bioCADDIE metadata entities. However, values of many metadata items of the nursing studies were not sufficiently represented through the bioCADDIE metadata. This was partly due to the differences in the scope of the content that the bioCADDIE metadata are designed to represent. The 194 nursing studies reported a total of 1, 181 unique data items, the majority of which take non-numeric values. This indicates the importance of data standardization to enable the integrative analyses of these data to support Big Data science in nursing.